Development of Assessment Instruments for Physics Problem Solving Skill in Accordance with Polya’s Stages - Johan Syahbrudin (Jurnal Pembelajaran Fisika, 2019)
This study aims to develop instruments measuring the ability to solve physics problems on the subject of high school gas kinetic theory based on Polya stages. This research is a research & development study using the 4D development model. Internal trials were conducted on 2 experts and 1 learning practitioner, while empirical trials were conducted on 81 students. Internal trial data were obtained through questionnaires and analyzed using descriptive analysis techniques, while empirical test results were obtained through test techniques and analyzed following the Rasch Model (RM) using the QUEST program. The results showed that at the internal test stage all items were stated to be very good in measuring the ability of solving physical problems. Empirical test results, as many as 5 out of 5 items were declared fit, with instrument reliability of 0.63 (high category). The level of difficulty of the items varies, some are easy and difficult. And the distinguishing power of all items included in either category. Thus, 5 test instruments developed were stated to meet the requirements and were appropriate to be used to measure the ability of solving physical problems based on Polya's stages.